2016
DOI: 10.1002/stc.1913
|View full text |Cite
|
Sign up to set email alerts
|

Semi-active control of flexible structures using closed-loop input shaping techniques

Abstract: In this research effort, a novel approach on the control of structures with magnetorheological (MR) dampers is presented, based on an appropriately adapted closed-loop version of the generic input shaping control theory. The MR damper is a very promising kind of semi-active control system (actuator), mixing the advantages of the active and passive structural control systems, hence their increasing use as attenuators that reject the effects of dynamic loads on civil engineering structures. The main contribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
(73 reference statements)
0
8
0
Order By: Relevance
“…On the basis of control engineering, many researchers have investigated and proposed various kinds of control methods for base‐isolated buildings with semi‐active dampers: an optimal controller‐based approach, such as linear‐quadratic‐regulator and linear‐quadratic‐Gaussian (LQG) controllers and H ∞ control (Sadek and Mohraz; Wongprasert and Symans; Nagarajaiah and Narasimhan; Xu et al; Li and Ou; and Wang and Dyke); fuzzy logic (Choi et al; Lin et al; and Ali and Ramaswamy); neural network (Lee et al; Reigles and Symans; Bani‐Hani and Sheban; and Fukukita et al); a sliding mode control (Singh et al and Zhao et al); a pseudo‐negative‐stiffness control (Iemura et al; Wu et al; and Gong and Xiong), and others (Nitta et al; Pozo et al; Tu et al; Rodriguez et al; Alqado et al; Vu et al; Ho et al). Shook et al conducted a comparative study for multiple control methods.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of control engineering, many researchers have investigated and proposed various kinds of control methods for base‐isolated buildings with semi‐active dampers: an optimal controller‐based approach, such as linear‐quadratic‐regulator and linear‐quadratic‐Gaussian (LQG) controllers and H ∞ control (Sadek and Mohraz; Wongprasert and Symans; Nagarajaiah and Narasimhan; Xu et al; Li and Ou; and Wang and Dyke); fuzzy logic (Choi et al; Lin et al; and Ali and Ramaswamy); neural network (Lee et al; Reigles and Symans; Bani‐Hani and Sheban; and Fukukita et al); a sliding mode control (Singh et al and Zhao et al); a pseudo‐negative‐stiffness control (Iemura et al; Wu et al; and Gong and Xiong), and others (Nitta et al; Pozo et al; Tu et al; Rodriguez et al; Alqado et al; Vu et al; Ho et al). Shook et al conducted a comparative study for multiple control methods.…”
Section: Introductionmentioning
confidence: 99%
“…Consider a hysteretic base‐isolated building structure as shown in Figure . The equation of motion of a seismically excited structure with multiple degrees of freedom that is controlled by a single active force acting on the base can be described as follows: boldMtruex¨+boldCtruex˙+boldKboldx=boldMboldΓtruex¨gboldΛf+boldΛu, where truex¨g is the absolute ground acceleration; boldx=[]xb,x1,x2,,xnTRn represents the horizontal displacement of the base and each floor of the structure with respect to the ground; n is the number of floors; truex˙ and truex¨ are the n + 1 dimensional vectors of the velocities and accelerations of the base and the floors of the structure; and M , C , and K are ( n + 1) × ( n + 1) mass, damping, and stiffness matrices, respectively, and have the following form: boldM=[]arraymnormalbarray0arrayarray0array0arraym1arrayarray0arrayarrayarrayarrayarray0array0arrayarraymn, boldC=[]arraycnormalb+c1arrayc1arrayarray0array0arrayc1arrayc1+c2arrayarray0array0arrayarrayarrayarraya...…”
Section: Control Designmentioning
confidence: 99%
“…Consider a hysteretic base-isolated building structure as shown in Figure 1. The equation of motion of a seismically excited structure with multiple degrees of freedom that is controlled by a single active force acting on the base can be described as follows [23][24][25] :…”
Section: System Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies used isolators or dampers to reduce vibration for high-tech buildings. [16][17][18][19][20][21][22][23] Hwang et al 16 studied the seismic protective systems for high-tech structures, and found that the incorporation of viscous dampers not only enhance the seismic safety but also minimize the micro-vibration of the structure. Lin et al 17 proposed a micro vibration mitigation system using viscous dampers for high-tech buildings, and results presented that the vibration can be effectively captured by the viscous damper and converted to lower frequencycontent tremors.…”
Section: Introductionmentioning
confidence: 99%